GE_GERICHTE P/8058/2012 vom 31. August 2021 - GE Cour de justice (2021)
IN DUBIO PRO REO;CALOMNIE | CP.303; CPP.389.al1; CPP.139.al2; CPP.433; CPP.428.al1; CPP.427.al1.leta; CPP.429.al1.leta; CPP.436.al1